Educational Disparities in Underdeveloped Regions: Limited Facilities, the Role of Teachers, and the Challenges of Digitalization - Tiara Desri Meisena; Azizah Amelia Kartika Sitorus; Jouse Mediansyah; Martha Heriniazwi Dianthi (Journal of Multidisciplinary Research, 2026)
Educational disparities in underdeveloped regions remain a persistent issue within the Indonesian education system. Limited educational facilities, the dominant role of teachers, and challenges in the implementation of educational digitalization are key factors affecting the quality of learning in these areas. This study aims to examine educational disparities in underdeveloped regions by analyzing limitations in educational facilities, the role of teachers, and the challenges of educational digitalization. The study employs a qualitative approach using a literature review method. Data were collected from academic journal articles, official government reports, documents from international organizations, and relevant online media published within the last five years. Data analysis was conducted using descriptive qualitative techniques through data reduction, data presentation, and conclusion drawing. The findings indicate that inadequate educational facilities remain a major barrier to effective learning in underdeveloped regions. Teachers play a critical role in sustaining educational processes; however, the heavy reliance on teachers reflects insufficient systemic support. Educational digitalization offers potential to reduce educational disparities, yet its implementation is constrained by limited technological infrastructure and uneven digital literacy. The study highlights the importance of integrated and context-sensitive policy approaches to address educational disparities in underdeveloped regions.